2020
DOI: 10.1186/s12939-020-01264-7
|View full text |Cite
|
Sign up to set email alerts
|

Disease experiences of female patients with Hansen’s disease residing in settlement in Korea

Abstract: Purpose: The purpose of this study was to identify female Hansen's disease experience in settlement village in Korea. Method: For this study, 11 participants in settlement village were purposively chosen. Data were collected through in-depth individual interviews from July to December 2015. Verbatim transcripts were analyzed following Colaizzi's phenomenological analysis to uncover the meaning of the experiences of the participants. Results: The study results showed that female Hansen's disease experience in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…All the studies used a qualitative approach or had a clearly reported qualitative component. There were nine studies based on the phenomenological approach [12,19,43,49,56,58,62,80,87], two were ethnographic studies [63,68], two used the grounded theory approach [55,78], and six were mixed methods [14,34,51,53,57,79], but only the India and Indonesia 1 [79] https://doi.org/10.1371/journal.pntd.0010761.t002…”
Section: Study Inclusionmentioning
confidence: 99%
See 4 more Smart Citations
“…All the studies used a qualitative approach or had a clearly reported qualitative component. There were nine studies based on the phenomenological approach [12,19,43,49,56,58,62,80,87], two were ethnographic studies [63,68], two used the grounded theory approach [55,78], and six were mixed methods [14,34,51,53,57,79], but only the India and Indonesia 1 [79] https://doi.org/10.1371/journal.pntd.0010761.t002…”
Section: Study Inclusionmentioning
confidence: 99%
“…The most frequently absent detail in the included studies was the information on the influence of the researcher on the research (question 7, S5 Appendix); only five studies reported this item. [34,45,58,62,73] Seventeen studies [12,19,43,44,47,59,63,65,[69][70][71][75][76][77]79,80,83] had no obvious statement locating the researcher culturally or theoretically.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations